Impact of Cytomegalovirus (CMV) on an Academic Pediatric Infectious Diseases Outpatient Clinic Referral Population, 2005-2020: Will the Advent of Universal Congenital CMV (cCMV) Screening Change Clinical Practice Referral Patterns? - Katelyn J. Rypka; Mark R. Schleiss (MDPI AG, 2024)
Cytomegalovirus (CMV) infections exert a substantial impact on the practice of pediatric infectious diseases. Although most infections in children are minimally symptomatic, several populations are at risk for CMV-associated disease, including immunosuppressed children, children with HIV infection, and, most significantly, children with congenital CMV (cCMV) infection. In spite of the ubiquitous nature of CMV infection, few studies have quantified the impact of CMV-associated care in a pediatric outpatient clinic setting. We evaluated the impact of CMV on clinical care in an outpatient clinic setting over a fifteen-year period at the University of Minnesota (UMN) Masonic Children's Hospital Pediatric Infectious Diseases (PID) Clinic. A retrospective review of clinic appointments identified 253 unique patients specifically evaluated over this time period for consideration of CMV infection. Of these, 242 were pediatric patients. The majority of the pediatric patients evaluated in the PID clinic were referred for either confirmed or suspected cCMV infection, including children referred for consideration of CMV as a potential reason for a failed newborn hearing screen (NHS) and/or for evaluation of CMV as a possible etiology for documented hearing loss. In total, 116 of the children evaluated during this time period (48%) were unequivocally confirmed as having cCMV infection, with an additional 37 (15%) presenting with presumed, probable, or possible cCMV infection. A total of 16 (7%) of the pediatric CMV cases were confirmed to be post-natally acquired infections. Of the 253 total patients, 11 (4%) of the referrals were for pregnant patients seeking advice about potential therapies in the setting of a known or suspected primary maternal infection during their pregnancies, with an attendant risk of fetal CMV infection. This overview of the demographics and referral patterns for patients evaluated for known or suspected CMV infections in a tertiary care center outpatient PID clinic will serve as a useful baseline assessment, even as future patterns of outpatient care are highly likely to evolve. We predict that PID clinic referrals for newborns identified by universal cCMV screening programs will result in a shift of the CMV outpatient population to healthier infants with clinically inapparent infections, and care will need to be taken by practitioners not to over-medicalize management for these asymptomatic newborns.